An almost-missed case of Ramsay-Hunt syndrome in a pediatric patient. - Goldberger, T.; Ramot, Y. (European Journal of Pediatric Dermatology, 2024)
Ramsay-Hunt syndrome is a rare form of herpes zoster, in which the skin lesions are associated with peripheral paresis of the facial nerve of variable intensity. It is less common but often more severe than idiopathic peripheral facial nerve palsy (Bell’s syndrome). A case is described with a favorable outcome in a 17-year-old girl.